Characterization of platelet gamma glutamyltransferase and its alteration in cases of atherosclerosis - ŞENER, AZİZE (LIPPINCOTT-RAVEN PUBL, 1995)
Among the various functional and biochemical alterations in the platelets of cases of atherosclerosis, the membrane alterations occupy an important place. The platelet intrinsic membrane protein gamma glutamyltransferase (GGT), which is involved in glutathione metabolism, has shown decreased activity in cases of atherosclerosis. To add new insights into the pathogenesis of atherosclerosis, GGT is characterized and correlated with other alterations. Triton X-100 solubilized membrane fractions of frozen and thawed platelets of atherosclerotic and normal subjects had 18.66 +/- 2.86 mU/10(9) platelets and 35.67 +/- 3.01 mU/10(9) platelets, respectively. The K-m values were the same, 2.08 mmol/L for gamma glutamyl-p-nitroanilide and 5.87 mmol/L for glycylglycine. The V-max values were reduced from 100 mU/10(9) platelets to 41.66 mU/10(9) platelets for gamma glutamyl-p-nitroanilide and from 45.45 mU/10(9) platelets to 38.46 mU/10(9) platelets for glycylglycine. Optimum pH of GGT activity was 8.2, and optimum temperature was 37 degrees C. It had thermal stability with a 64% relative activity at 56 degrees C for 30 min. Serine against berate was detected as the competitive inhibitor and bromcresol green as the noncompetitive inhibitor. In vivo administration of the antithrombotic drug defibrotide increased the platelet GGT levels to those of normals, from 14.72 +/- 7.27 mU/10(9) platelets to 31.80 +/- 12.21 mU/10(9) platelets in 2 hs. Cholesterol, high-density lipoprotein cholesterol in the membrane fractions, and platelet glutathione levels were unaltered. The lipid peroxidation (membrane malondialdehyde) level was increased, and glucose and histidine active transport systems were impaired in atherosclerotics. All of these changes are discussed in relation to GGT.
Keywords: human platelets; atherosclerosis; gamma glutamyltransferase; gamma glutamyl transpeptidase; defibrotide; biological membranes; GLUTAMYL-TRANSFERASE TRANSPEPTIDASE; HUMAN LIVER; TRANSPORT; KIDNEY; PURIFICATION; MEMBRANE